Ironie pas morte : Nicolas Mathieu contre le politiquement correct
Irony is a: 1/non-literal 2/ contradictory 3/ and offensive statement; it implies a contradiction which opposes 1/ what is said et what is meant (antiphrasis); 2/ what is said and what is referred to (irony is crucially context-sensitive); what is said by the speaker and what is generally agreed (the domain of common belief or probable knowledge, doxa in Greek, is more often than not the aim of irony). Irony opacifies communication. It creates a gap between those who love and understand it and the others: therefore it is not inclusive. It challenges the scruples of political correctness. Nicolas Mathieu’s realistic novels mock the European subalterns; what is the point of this unconventional literary strategy?